Simple Solutions to Complex Catastrophes Dialectics of Peace, Climate, Finance, and Health - Braithwaite, John (Sustainable Development Goals Series, 2024)
This open access book sets out simple solutions to managing complex catastrophes. It focusses on four kinds of crises - climate change, crime-war cascades, epidemics and financial crises. These catastrophes are conceived as complex and prone to cascade effects. This book is optimistic in explaining that there are identifiable simple institutions that international society can strengthen and some simple principles that can help humankind to control the expanding gamut of complex catastrophes that confront the planet including simple, stable institutions and regulatory bodies. It draws on a wide range of current and past crises and challenges, from the Cold War to COVID-19, and from Weapons of Mass Destruction to restorative diplomacy with States like China, to provide an urgent and timely path forward. It speaks to those interested in criminology, public policy and international relations, political science, sociology, public health and economics. John Braithwaite is Emeritus Distinguished Professor of the Australian National University and an interdisciplinary scholar of peacebuilding, war crime, business crime, criminological theory, and regulation and governance. He founded and was the first Director of the School of Regulation and Global Governance (RegNet) at ANU. Many of his previous works can be downloaded from johnbraithwaite.com.